Factors Influencing Do-Not-Resuscitate Status in Children During Last Month of Life: Single Institution Experience. Issue 4 (May 2019) - Moaed, Bilal; Mordechai, Oz; Weyl Ben-Arush, Myriam; Tamir, Sharon; Ofir, Ruth; Postovsky, Sergey
Abstract : Background: It is currently expected that about 20% of children with cancer will ultimately die. Writing advanced life directives sufficiently long before the actual death of a child ensues allows both parents and medical staff to develop optimal treatment plans in the best interests of the child. Aim of the study: The aim of the study was to evaluate factors that may influence the process of decision-making regarding Do-Not-Resuscitate (DNR) status. Methods: Retrospective single institution study. Results: Totally, 79 patients died between September 01, 2011 and August 31, 2017. Median age of the children was 10.5 years (range, 1 to 24 y). Forty-five were males. There were 37 Muslims, 27 Jews, 9 Druze, and 6 Christians. Twenty-one patients had sarcomas, 20 had CNS tumors, 10 had neuroblastoma, 17 had leukemias/lymphomas, 11 had carcinomas, and other rare tumors as well as nonmalignant diseases. No statistically significant association between all evaluated factors and DNR order status was found. Conclusions: It is possible that, other than demographic, clinical-associated, or therapy-associated factors play an important role in the process of decision-making regarding DNR. We feel that sincere communication between parents, their child (when appropriate) and medical and psychosocial staff may have a more crucial role when such decisions have to be made.